2012
DOI: 10.1289/ehp.1003096
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Concentrations of Polyfluoroalkyl Compounds during Pregnancy and Fetal and Postnatal Growth in British Girls

Abstract: Background: Prenatal exposures to polyfluoroalkyl compounds (PFCs) may be associated with adverse changes in fetal and postnatal growth.Objective: We explored associations of prenatal serum concentrations of perfluorooctane sulfonate (PFOS), perfluorooctanoate (PFOA), and perfluorohexane sulfonate (PFHxS) with fetal and postnatal growth in girls.Methods: We studied a sample of 447 singleton girls and their mothers participating in the Avon Longitudinal Study of Parents and Children (ALSPAC). Data on weight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
195
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(213 citation statements)
references
References 29 publications
11
195
4
3
Order By: Relevance
“…PFOS, PFOA, PFNA and PFHxS, and indices of foetal growth/development, including birth weight, birth length, ponderal index, gestational age, and pre-term birth, have been conflicting. Some have shown increased levels to be inversely related (Andersen et al, 2010;Apelberg et al, 2007;Fei et al, 2007;Wu et al, 2012;Darrow et al, 2013, Maisonet et al, 2012Wang et al, 2011), whereas others have reported no effect or an opposite association (Fei et al, 2008b, Hamm et al, 2010Olsen et al, 2009).…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…PFOS, PFOA, PFNA and PFHxS, and indices of foetal growth/development, including birth weight, birth length, ponderal index, gestational age, and pre-term birth, have been conflicting. Some have shown increased levels to be inversely related (Andersen et al, 2010;Apelberg et al, 2007;Fei et al, 2007;Wu et al, 2012;Darrow et al, 2013, Maisonet et al, 2012Wang et al, 2011), whereas others have reported no effect or an opposite association (Fei et al, 2008b, Hamm et al, 2010Olsen et al, 2009).…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…For instance, Fei et al found that maternal serum levels of PFOA were inversely associated with birth weight among newborns from the Danish national birth cohort [9] . This was supported by Maisonet et al who found that British girls born to mothers with PFOA, PFOS and PFHxS concentrations in the upper tertile on average weighed less than those in the low tertile [10] . However, 20 months after the birth, the girls born to mothers with PFOS concentrations in the upper tertile weighed significantly more than those in the lowest tertile.…”
mentioning
confidence: 71%
“…Data from a subgroup of the Norwegian Mother and Child Cohort study (n = 901 women; 2003-2004) showed lower birth weight among infants born to mothers in the highest quartiles of PFOA (and PFOS) compared to lowest quartiles (Whitworth et al, 2012a). Also a British study found that girls born to mothers with maternal serum concentrations of PFOA in the upper tertile weighed less (130 g (95%CI: -237, -30)) at birth compared with girls born to mothers with serum concentrations in the lower tertile (Maisonet et al, 2012). Contrary to the above findings, 2 smaller Canadian studies found no evidence of decreased birth weight and maternal PFOA levels (Monroy et al, 2008;Hamm et al, 2010).…”
Section:  Developmental Outcomementioning
confidence: 99%
“…The most extensive set of studies has examined foetal growth, birth weight, duration of gestation, and related indices of in utero development (Apelberg et al, 2007;Fei et al, , 2008Hamm et al, 2010;Hoffman et al, 2010;Monroy et al, 2008;So et al, 2006;Washino et al, 2009;Maisonet et al, 2012). In the Danish National Birth Cohort study (DNBC) (n = 1,400 mother/child), Fei et al investigated the possible correlations between the concentration of PFOA (and PFOS) in the maternal blood during the first and second trimesters of pregnancy and the birth weight and risk of premature birth .…”
Section:  Developmental Outcomementioning
confidence: 99%
See 1 more Smart Citation